A home in the swamp - Lion, David C., 1948-; David C. Lion (New York : Childrens Press, 2007)
Have you ever visited a swamp? It's warm in a swamp and the ground is wet. Swamps are home to many interesting plants and animals.
Includes bibliographical references (p. 24) index.
Keywords: Swamp ecology -- Juvenile literature; Swamp -- Juvenile literature